CHILD ABUSE AS THE CAUSATIVE FACTOR FOR MULTIPLE PSYCHOLOGICAL AFFLICTIONS IN LATER LIFE - Madhurendra Kishore Madhur (International Journal of Multidisciplinary Research and Studies, 2021)
The link between traumatic experiences in childhood and negative health consequences in adulthood is extremely well documented. Regrettably, despite the vast amount of research that has been conducted to prove the existence of this connection, the mainstream medical literature very seldom mentions it. In a recent review article on depression that was published in the New England Journal of Medicine, the author failed to make even a passing reference to the well-documented link between adult depression and childhood abuse. This highlights the necessity for research that is more visible and that will reach physicians, who provide the majority of front-line health care. No mention of the significance of childhood maltreatment as a risk factor is included in the otherwise exhaustive national recommendations on depression in primary care that were published in 1993. These guidelines were produced in 1993.